Fitness to stand trial: fairness first and foremost - Schneider, Richard D. (Irwin Law, 2018)
"Of all the issues that bring mental health practitioners and the criminal courts together, fitness to stand trial is by far the most common. In Canada, thousands of fitness assessments, psychiatric reports, fitness hearings, and verdicts of either “fit” or “unfit” to stand trial are rendered every year. For such a common event, one would be inclined to think that, for the most part, the law is uncontroversial; that most of the issues have been settled. Fitness to Stand Trial lays out the law as it is seemingly settled, and discusses several areas where the law is much less settled."–Résumé de l'éditeur.
QID: Q135479506